The Impact of Student Psychological Factors on Self-Regulation in Learning in Primary Schools - Susanto, Ratnawati; Nasution, Evi Syafrida; Sanulita, Henny; Lumbantoruan, Jitu Halomoan (Universitas Pendidikan Indonesia, 2024)
Regulation in effective learning can achieve knowledge and understanding of the material. However, in reality in the field, student self-regulation is still low. This is urgent to research because there are differences in theory, expectations, and reality in the field, so the research aims to analyze the influence of psychological factors on elementary school students' regulatory learning. The psychological factors studied are self-efficacy, orientation, and beliefs about intelligence. Quantitative research methods. The subjects were elementary school students with a sample of 639. The data collection technique used an instrument with the Beliefs of Intelligence Scale. Analysis techniques using Statistics version 25.0 with the Pearson correlation r test and Stepwise Multiple Regression analysis were used to analyze the research data. The results and findings show that the Regression Model of intrinsic goal orientation, self-efficacy, and entity trust contributes 31.3% in the good category. Change variance in self-regulated learning. The influence of intrinsic goal orientation is the highest, followed by self-efficacy and entity trust. This self-psychology model contributes to elementary school students' self-regulation learning. In conclusion, self-psychological factors must be considered to produce students who are more independent in independent learning. This research means that schools can shape student psychology independently.